Inventory and utilization of the family Rubiaceae in the forests of Desa Serdang, Barusjahe, Karo, North Sumatra - Aisyah Karina Putri,; Wina Dyah Puspita Sari,; Yusran Efendi Ritonga, (Bioma, 2024)
Rubiaceae is a common forest plant family in Indonesia, including in many community-managed village forests such as the Serdang Village Forest in Barusjahe, Karo, North Sumatra. A thorough inventory of rubiaceous species is needed to understand their composition and usage by local people. This study aims to list all Rubiaceae species, understand their morphological characteristics, and document their utilization in the village forest. The exploration identified 18 species of Rubiaceae from 12 different genera. Nine species are utilized by the local community: four species as traditional medicine, two species as ornamental plants, one species for firewood, and one species for house/garden posts and household tools. This research enhances the understanding of Rubiaceae species and their uses in the Desa Serdang village forest.